2006
DOI: 10.1248/cpb.54.1276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Moisture Content in Aerosol on the Spray Performance of Stmerin D HFA Preparations

Abstract: The pressurized metered dose inhaler (MDI) is a convenient and promising technology for drug delivery to the respiratory tract. For example, steroid MDIs have been applied to the topical therapy instead of oral administration which causes severe systemic side effects such as notable suppression of the hypothalamic-pituitary-adrenal axis, nephrosis, gastric ulcer, moon face and so on. As the topical therapy with MDI improves the therapeutic index by about 10 to 50 times, i.e., increase the local concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…2). These results are consistent with our previous study, 3) which demonstrated that the moisture penetration of the MDI during storage influenced the spray performance, and that the FPD drastically decreased and dose content uniformity was inconsistent when moisture content exceeded 300 ppm. There are some reports on the influences of the moisture uptake into the MDIs on the product stabilities, 6,7) i.e., i) crystal growth might be occurred when solubility of the drug substance in the propellants would be increased or decreased, ii) chemical degradation might be occurred when the drug substances are easy to be hydrated and degradable to the water.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2). These results are consistent with our previous study, 3) which demonstrated that the moisture penetration of the MDI during storage influenced the spray performance, and that the FPD drastically decreased and dose content uniformity was inconsistent when moisture content exceeded 300 ppm. There are some reports on the influences of the moisture uptake into the MDIs on the product stabilities, 6,7) i.e., i) crystal growth might be occurred when solubility of the drug substance in the propellants would be increased or decreased, ii) chemical degradation might be occurred when the drug substances are easy to be hydrated and degradable to the water.…”
Section: Discussionsupporting
confidence: 93%
“…2) Our previous study demonstrated that the spray performance of a suspension MDI using hydrofluoroalkanes (HFA134a and HFA-227) was sensitive to moisture content, and that moisture could penetrate the canister under accelerated stress conditions at 40°C and 75% relative humidity (RH). 3) This study found that increased moisture content significantly reduced the uniformity of the aerosol delivered dose due to an increase in drug aggregation in the liquid HFA and a reduction of the suspension homogeneity. Further, the moisture strongly affects the particle size distribution after actuation because moisture reduces the propellant evaporation rate and increases the apparent particle size.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The United States Pharmacopeia (1995) also reported its use on slow-flowing propellant gas streams fed into the reagent at 100 mL/min. Although the technique has been applied to MDI formulations (Kim et al, 1992;Kulphaisal et al, 2002;Murata et al, 2006;Williams III & Chengjiu, 2000;Williams III & Hu, 2000;Williams III et al, 1997), its accuracy for rapidly evaporating boli of pressurised gas is not satisfactorily reported hitherto. The aerosol might bubble too fast through the liquid reagent and vaporise into the titration cell headspace without sufficient mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Since HFAs are more polar and more hygroscopic than CFCs (Williams, 1999;Williams III, Jie, & Koleng, 1997) water ingress is more significant in HFA MDIs. Ambient moisture diffuses into MDIs through the valve gaskets (Miller, 1990;Reynolds & McNamara, 1996;Williams, 1999) and adversely affect the physical stability of MDI formulations by promoting drug particle growth and aggregation (Murata, Ito, Izumi, & Chikushi, 2006;Williams III & Hu, 2000).…”
Section: Introductionmentioning
confidence: 99%